Christianity, masculinity and authority in the life of George Sarawia - Samson, Jane (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2009)
George Sarawia was ordained in 1873 as the first Melanesian Anglican priest. This article presents preliminary research findings concerning the various constructs of masculinity deployed by Sarawia, his indigenous community, and the mission. A high-ranking member of the indigenous men's society, and part of an extended family, Sarawaia integrated Christian concepts of brotherhood and fatherhood with controversial results. Some of his fellow missionaries accused him of leading his people more as an indigenous big-man than as a priest. The article contends that the career of George Sarawia revealed a negotiation, rather than an imposition, of masculinities reflecting indigenous as well as western priorities.